2007
DOI: 10.1158/0008-5472.can-06-3587
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogen-Specific Gene Expression Profiles in Short-term Treated Eker and Wild-type Rats Indicative of Pathways Involved in Renal Tumorigenesis

Abstract: Eker rats heterozygous for a dominant germline mutation in the tuberous sclerosis 2 (Tsc2) tumor suppressor gene were used as a model to study renal carcinogenesis. Eker and corresponding wild-type rats were exposed to genotoxic aristolochic acid (AA) or non-genotoxic ochratoxin A (OTA) to elucidate early carcinogen-specific gene expression changes and to test whether Eker rats are more sensitive to carcinogeninduced changes in gene expression. Male Eker and wild-type rats were gavaged daily with AA (10 mg/kg … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
41
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 41 publications
10
41
3
Order By: Relevance
“…An increase in the expression of cell cycle genes is a common finding with a number of renal nephrotoxins and renal carcinogens. [21][22][23] The enrichment of the cell cycle genes after short term exposure is consistent with the small increase in cell proliferation observed in the kidney after 7 days exposure to MON. 13 Some of the gene increase is involved in cell division with role in chromosome stability, alignment and segregation and we cannot at this stage rule out the possibility of adverse chromosomal events in the kidney following MON.…”
Section: In Vivo Studiessupporting
confidence: 75%
“…An increase in the expression of cell cycle genes is a common finding with a number of renal nephrotoxins and renal carcinogens. [21][22][23] The enrichment of the cell cycle genes after short term exposure is consistent with the small increase in cell proliferation observed in the kidney after 7 days exposure to MON. 13 Some of the gene increase is involved in cell division with role in chromosome stability, alignment and segregation and we cannot at this stage rule out the possibility of adverse chromosomal events in the kidney following MON.…”
Section: In Vivo Studiessupporting
confidence: 75%
“…Toxicogenomics can provide the means to define relationships between toxicological endpoints and gene expression patterns, predict toxic responses, and identify mechanisms of toxicity of environmental agents such as AA Guo et al, 2006;Stemmer et al, 2007). In order to examine the role of TP53 in cellular responses to AA we have used cDNA microarrays to analyse transcriptional responses in a pair of human colorectal cell lines (HCT116) that differ in TP53 status (i.e.…”
mentioning
confidence: 99%
“…Our results also showed a reduction in this gene. Male Tsc2 EKER rats gavaged with OTA also changed their energy provision 43 . In addition, liver lipid metobolism was down-regulated of male F344 rats after OTA treatments in several studies 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…the role of biotransformation in OTA toxicity has already been addressed in previous studies. Some of these investigators reported a down-regulation in the expression of the representative genes of transporters and xenobiotic metabolism 30,42 , while the remaining reports found an elevation in their expression 43 . Furthermore, energy metabolism was deregulated induced by OTA in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%